EFFECT OF ADVERTISING, PRODUCT SUPERIORITY, LIFE STYLE AND PRICE ON THE PURCHASE DECISION OF THE LE-MINERALE MINERAL WATER BRAND (Case Study On Malaya Mart and Ranggon Mart In Bangkinang City) - Imelda Dewi Sartikawati; Auzar Ali; Adi Setiawan (Jurnal Riset Manajemen Indonesia, 2020)
Research to determine the effect of advertising, product superiority, life style and price on the purchase decision of the le-minerale mineral water brand (case study on Malaya Mart and Ranggon Mart in Bangkinang City). Types and sources of data used in this study are primary data and secondary data, while data collection techniques used in this study were questionnaires, file research, observation and interviews. Based on the Slovin formula, the number of samples in this study was 100 consumers consisiting of 60 consumers at Malaya Mart and 40 consumers at Ranggon Mart. The sample was taken using accidental sampling technique. Based on the simulthan and partial test results, the variable of advertising, product superiority, life style and price have a significant effect on the purchase decision of the le-minerale mineral water brand (case study on Malaya Mart and Ranggon Mart in Bangkinang City).The closeness of the relationship that occurs between the atractiveness of advertising, product superiority, life style and price on the purchase decision of the le-minerale mineral water brand (case study on Malaya Mart and Ranggon Mart in Bangkinang City) is very strong with a correlation coefficient R of 86%. While contribution of independent variables to the dependent variables is equual to 72.9% while the remaining 27.1% is influenced by other variables not examined in this study.